Molecular Detection blaOXA50 gene of P.aerginosae Isolated from Otitis Media - Ahmed Maki N. Al-Muaala1 , Noor A.Neama2 , Thulfikar H. al-kefaei1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pseudomonas aerugenosa is a gram negative rod shape bacterium belonging to the family Pseudomonadaceae . Pseudomonas aeruginosa is a major uropathogen in a hospital. It can tolerate a wide kind of physical conditions and many antibiotics via several mechanisms resistance . The study included genetic study blaOXA50 gene utilizer technique PCR by specific forward and reverse primers to common bacteria that causes otitis media, 40 isolated from otitis media patients (ear swab). Primary identification was depended on Gram stain ,biochemical tests and vitek 2 system was done . The results demonstrate 30 isolate of them were P.aerginosae. The result appear P.aerginosae contain on 25(19%) blaOXA50 gene.